The THE EFFECT OF ACNE VULGARIS ON QUALITY OF LIFE AMONG RURAL PATIENTS: A CROSS-SECTIONAL STUDY - RUCHIKA TRIPATHI; UDAY PRABHAKAR; RAJARAM YADAV (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Acne vulgaris affects a large majority of adolescents, often extending into adulthood. The aim of the study was to determine its impact on the quality of life (QoL). Methods: This was a cross-sectional, questionnaire-based study, conducted on 60 patients, who attended the dermatology outpatient department and were diagnosed with acne vulgaris by the physician. The severity of lesions was assessed using the global acne grading system, and QoL was assessed using the dermatology life quality index (DLQI) questionnaire. Statistical analysis was done to assess any possible association between DLQI with severity and sequelae of acne vulgaris. Results: The mean DLQI score was 5.46. There was a significant association between DLQI and severity of acne grade (p<0.05). Conclusion: There is a significant impact of acne on QoL, and hence, a holistic approach is required to treat it.